A pharmacy asthma service achieves a change in patient responses from increased awareness to taking responsibility for their asthma. (4th July 2014) - Naik‐Panvelkar, Pradnya; Saini, Bandana; LeMay, Kate S.; Emmerton, Lynne M.; Stewart, Kay; Burton, Deborah L.; Bosnic‐Anticevich, Sinthia Z.; Krass, Ines; Smith, Lorraine D.; Armour, Carol L.
Abstract Objectives If novel health services are to be implemented and sustained in practice, the perceptions and views of patients form a critical part of their evaluation. The aims of this study were to explore patient's perceptions and experiences with a pharmacy asthma service and to investigate if there was a change over time. Methods Interviews and focus groups were conducted with patients participating in the asthma service at three time points. Data were transcribed verbatim and thematically analyzed using a framework approach. Key findings The service led to an enhanced awareness and understanding of asthma, changes in participants' beliefs and attitudes towards asthma management, changes in asthma‐related health behaviours and improved self‐efficacy. Participants were very positive about the service and the role of the pharmacist in asthma management. There was a shift in participant perceptions and views, from being at an abstract level in those who had completed just one visit of the service to a more experiential level in those who had experienced the entire comprehensive asthma service. Conclusions A sustained experience/multiple visits in a service may lead to more concrete changes in patient perceptions of severity, beliefs, health behaviours and enhanced self‐efficacy and control. The study highlights a need for such asthma services in the community.